Empowering Hospital Staff to Enhance Service Excellence: A Community-Based Intervention in Central Java - Sylvia Samuel; Hendra Achmadi; Margaretha Pink Berlianto; Dewi Wuisan; Yohana Meilani Palupi (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study reports on a community service project conducted at Rumah Sakit Baptis, Central Java, to improve hospital service excellence through staff empowerment. The project addressed key challenges, including weak interdepartmental collaboration, ineffective communication, difficulties in delivering sensitive information, and limited awareness of patient-centered service quality. Using a participatory approach, the intervention included workshops, role-playing exercises, counseling sessions, and the introduction of standardized communication protocols. The results showed clear improvements in staff competencies, particularly in empathy, teamwork, and communication with patients and families. Staff reported greater confidence in handling sensitive conversations, while patients observed a more approachable and responsive service. Cross-departmental collaboration also improved, resulting in reduced delays and enhanced coordination. Initial patient satisfaction surveys indicated a positive shift in perceptions of care quality. These findings highlight that even in resource-limited hospital contexts, meaningful improvements can be achieved through structured training and cultural change. The project contributes both practical recommendations for hospital management and theoretical insights by applying the SERVQUAL and patient-centered care frameworks to the Indonesian healthcare setting.